Curriculum development: panacea or poison? - Terence Nigel Mitchell (Universidad de Deusto, 2015)
The November 2014 issue of the Tuning Journal appeared under the theme "Policy and Implementation: Actions for Curriculum Reform". This article is a personal reflection on the role of curricula in achieving the aims of the European Higher Education Area (EHEA) and beyond. Its background is the postulate that the most important goals of the Bologna Process are essentially the improvement of mobility and recognition at all levels of higher education. Curricula can be used to encourage mobility and recognition or to hinder them, but as an element of the education process they have been treated very unevenly during the development of the EHEA. Well-designed curricula are vital, but must not be misused. In the European climate of today, the development of regional, national or even international curricula is neither possible nor necessary.